Ekspansi Pasar dan Peningkatan Kualitas UMKM Sepatu Desa Gemawang, Kabupaten Semarang Melalui Kegiatan Pelatihan - Diah Winarti; Annisa Peby Amalya; Febriana (Forum Kerjasama Pendidikan Tinggi, 2021)
The pandemic that occurred about 1 year ago had an impact on the decline in the economy. Small business units in Gemawang Village felt the impact, such as decreased sales, capital, hampered distribution, and difficulty in raw materials. Digital-based business development is an alternative to saving the business unit sector during the Covid-19 pandemic. Business units in Gemawang Village experienced various problems such as difficulties in marketing batik shoe products online due to the lack of workers and the ability to utilize technology. The purpose of community service activities is to increase the amount of production from each business unit along with increasing turnover, modifying packaging, prices, shapes, expanding product marketing by selling through digital markets from related units, improving branding, educating each unit in the use of e-commerce., marketing, and good packaging, optimizing the utilization of village potential and increasing the income of each production unit and the community around Gemawang Village. The results of community service show results that can increase people's income through the production of shoes that look more varied, attractive and fashion. The model is not monotonous and when used it is more comfortable on the feet with varied and quality packaging. Community service activities carried out by the IAAS UNDIP team to the community in Gemawang village are very useful and can increase the amount of production from each business unit along with an increase in turnover. People are highly motivated to produce their shoes by modifying the packaging, model, and shape. Thus, it will expand product marketing, increase branding, so that it can increase the income of the Gemawang village community